A Novel Approach on the Advancement in Polymer Phase Change Material in Solar Energy - G. Jegan; P. Ramani; T. J. Nagalakshmi; S. Chitra; T. Samraj Lawrence (International Journal of Photoenergy)
A wide interest has been shown in the application of solar energy in recent times. This motivated the researchers to make a development in the approach of solar energy, but there are different technologies like MPPT, CPG, and grid mode that have been used to maintain a constant temperature. Among these, phase change material has been used to regulate the temperature in the system. Solar energy is becoming an essential approach for increasing the efficiency of thermal energy conversion and utilizing polymeric step change composites, which have attracted extremely large interest in recent years due to their advantages of high energy density and powerful energy output stability. A plethora of reviews and reports have been published to compile the diverse range of PCMs made available for various applications. PCMs are created by improving thermophysical thermodynamic stability, latent heat, and heat capacity. Furthermore, the possible applications of polymer phase PCMs in a variety of fields, such as energy storage devices, thermal corrective action, and temperature-controlled drug carriers, are detailed. In this paper, a novel approach on the advancement of nanoconfined phase change material is defined along with the application of the solar energy system.